The Comparison of Participation Motives of Male and Female Older Adults for Sport Activities in Tehran - Mahvash Nourbakhsh; Ahmad Farokhi; Saiede Khakpour; Homayon Farahani (University of Tehran, 2010)
The purpose of this study was to investigate and compare the participation motives of male and female older adults for sport activities. The subjects were 241 persons (121 men and 120 women ranged from 60 to 89 years old, M = 66.16, SD = 6.66) who were selected from 5 districts of Tehran by relative portion method. Data were collected using demographic questionnaire and participation motivation questionnaire for older adults (PMQOA). The descriptive statistics, Friedman test and one-way analysis of variance (ANOVA) were used to describe variables and to test the research hypotheses. Results indicated significant differences in the priority of different factors of participation motives (X2 = 556.4, P=0.00); and fitness motive was the most important reason for sport participation in older adults. There were significant differences between men and women in "medical" and "reputation" factors (P